Beyond functional diversity: The importance of trophic position to understanding functional processes in community evolution - Banker, Roxanne M. W.; Dineen, Ashley A.; Sorman, Melanie G.; Tyler, Carrie L.; Roopnarine, Peter D. (Frontiers in Ecology and Evolution, 2022)
Ecosystem structure, that is the species present, the functions they represent, and how those functions interact, is an important determinant of community stability. This in turn affects how ecosystems respond to natural and anthropogenic crises, and whether species or the ecological functions that they represent are able to persist. Here we use fossil data from museum collections, literature, and the Paleobiology Database to reconstruct trophic networks of Tethyan paleocommunities from the Anisian and Carnian (Triassic), Bathonian (Jurassic), and Aptian (Cretaceous) Stages, and compare these to a previously reconstructed trophic network from a modern Jamaican reef community. We generated model food webs consistent with functional structure and taxon richnesses of communities, and compared distributions of guild level parameters among communities, to assess the effect of the Mesozoic Marine Revolution on ecosystem dynamics. We found that the trophic space of communities expanded from the Anisian to the Aptian, but this pattern was not monotonic. We also found that trophic position for a given guild was subject to variation depending on what other guilds were present in that stage. The Bathonian showed the lowest degree of trophic omnivory by top consumers among all Mesozoic networks, and was dominated by longer food chains. In contrast, the Aptian network displayed a greater degree of short food chains and trophic omnivory that we attribute to the novel presence of large predatory guilds, such as sharks and bony fish. Interestingly, the modern Jamaican community appeared to have a higher proportion of long chains, as was the case in the Bathonian. Overall, results indicate that trophic structure is highly dependent on the taxa and ecological functions present, primary production experienced by the community, and activity of top consumers. Results from this study point to a need to better understand trophic position when planning restoration activities because a community may be so altered by human activity that restoring a species or its interactions may no longer be possible, and alternatives must be reached to restore an important function. Further work may also focus on elucidating the precise roles of top consumers in moderating network structure and community stability.